UNIT 17.14 Diagnosing Lysosomal Storage Disorders: Mucopolysaccharidosis Type II. (18th October 2013) - Johnson, Britt A.; van Diggelen, Otto P.; Dajnoki, Angela; Bodamer, Olaf A.
Abstract: Mucopolysaccharidosis type II (MPS II) is an X‐linked lysosomal storage disorder caused by a deficiency of iduronate 2‐sulfatase (IDS). Progressive, intralysosomal accumulation of the glycosaminoglycans (GAGs) dermatan and heparan sulfate in almost all tissues leads to multi‐organ involvement in affected males but to virtual absence of symptoms in heterozygote female carriers due to preferential inactivation of the mutant allele. Diagnosis of MPS II in males is based on IDS analysis in leukocytes, fibroblasts, plasma, or dried blood spots (DBS), whereas IDS activities may be within the normal range in heterozygote females. The advent of fluorometric and mass spectrometry methods for enzyme analysis in DBS has simplified the diagnostic approach for MPS II males. Molecular analysis of the IDS gene confirms the diagnosis of MPS II in males and is the only diagnostic test to confirm carrier status in females. This unit provides detailed analytical protocols for measurement of IDS activity in DBS and plasma using a fluorometric assay. Curr. Protoc. Hum. Genet . 79:17.14.1‐17.14.9. © 2013 by John Wiley & Sons, Inc.